Editorial Introduction - Suzanne Porath (Networks: An Online Journal for Teacher Research, 2016)
Action research comes in various forms such as teacher inquiry, participatory action research, practitioner research, and cooperative inquiry. But, as Bradbury’s introduction to the third edition of the SAGE Handbook of Action Research highlights, “It brings together action and reflection, theory and practice, in the pursuit of practical solutions to issues of pressing concern.” The articles in this eighteenth volume of Networks: An Online Journal for Teacher Research illustrate the unique combination of action and reflection, theory and practice that leads to increased knowledge and understanding of educator practice across grade levels and subject areas.